2017
DOI: 10.3390/f8040113
|View full text |Cite
|
Sign up to set email alerts
|

A Tree Species Effect on Soil That Is Consistent Across the Species’ Range: The Case of Aspen and Soil Carbon in North America

Abstract: Trembling aspen covers a large geographic range in North America, and previous studies reported that a better understanding of its singular influence on soil properties and processes is of high relevance for global change questions. Here we investigate the potential impact of a shift in aspen abundance on soil carbon sequestration and soil carbon stability at the continental scale by conducting a systematic literature review using 23 published studies. Our review shows that aspen's effect on soil carbon is rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 104 publications
4
27
0
Order By: Relevance
“…The SOC stocks found in the mineral soils at TWDEF are comparable to values found in other areas in North America [49][50][51][52]. However, aspen do not always have higher SOC stocks than conifers [53]. Laganiére et al [52] found higher mineral SOC pools under aspen in Ontario, but not in Quebec.…”
Section: Soc Pools and Biotic And Abiotic Controls On Soc And Momsupporting
confidence: 58%
See 1 more Smart Citation
“…The SOC stocks found in the mineral soils at TWDEF are comparable to values found in other areas in North America [49][50][51][52]. However, aspen do not always have higher SOC stocks than conifers [53]. Laganiére et al [52] found higher mineral SOC pools under aspen in Ontario, but not in Quebec.…”
Section: Soc Pools and Biotic And Abiotic Controls On Soc And Momsupporting
confidence: 58%
“…Also, Laganiére et al [56] found a higher proportion of SOC distributed as LF in conifer soils, and higher CO2 evolution from these soils during incubation [52]. Overall, higher stability of aspen SOC seems to be a consistent finding in literature, as reviewed by Laganiére et al [53]. The strong correlation between root and LF C suggests that the major source of LF in the deeper depths is root detritus.…”
Section: Soc Pools and Biotic And Abiotic Controls On Soc And Mommentioning
confidence: 60%
“…To examine these hypotheses and other effects of tree species on SOM stability in mineral soils, we used a common garden with replicated, monoculture plots of eleven tree species to investigate the impact of 17 ecological factors on five different indicators of SOM stability: heterotrophic respiration from incubated soils, the proportion of total SOM present in relatively stable SOM pools (including C in POM <20 µm and C in MOM <20 µm; Mueller et al, ), and the relative abundance of both 14 C and 15 N in bulk SOM. Although previous studies from this common garden in Poland and similar plantations in Denmark have investigated the effects of litter traits on C stocks in mineral soils (Mueller, Eissenstat, et al, ; Mueller et al, ; Vesterdal, Clarke, Sigurdsson, & Gundersen, ), these studies provide limited information on SOM stability because it can vary independently of SOM stocks (Frank, Pontes, & McFarlane, ; Laganière et al, ). Here, the ecological factors investigated included chemical properties of leaf litter and fine roots, estimates of the magnitude of organic inputs to soil, rates of decomposition and turnover for leaf litter, fine roots, and the organic horizon, key descriptors of the soil biotic community, and physicochemical soil properties.…”
Section: Introductionmentioning
confidence: 99%
“…This potential varies with tree species, which can substantially impact soil organic C pools (e.g., Cremer, Kern, & Prietzel, 2017;Dawud et al, 2016;Mueller et al, 2015). Little information, though, is available on the impacts of different tree species on the stability of organic C in soil (Ahmed, Smith, Jones, & Godbold, 2016;Augusto et al, 2015;Laganière, Boča, Van Miegroet, & Paré, 2017). Because tree species composition in forests is dynamic (Ellison et al, 2005;Fisichelli, Frelich, & Reich, 2014;Leithead, Anand, & Silva, 2010), particularly under a changing climate (Iverson & Prasad, 2001;Reich et al, 2015;Zolkos et al, 2015), a more detailed knowledge of tree species effects on soil C stabilization is crucial for predicting the persistence of soil C in forest ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…However, limitations due to the use of traditional techniques hinder an accurate evaluation of soil microbial taxa, which has greatly delayed our understanding of several core ecosystem processes, such as variations in microbial communities, soil C accumulation, ecosystem succession, and ecosystem functions [20,21]. Identifying and quantifying the relative influence of root-microbial systems in forests remains a challenge for researchers [22]. Thus, there is still a limited understanding of the relationship between soil microbial taxa and soil C accumulation in a changing environment, especially in restored forest ecosystems.…”
Section: Introductionmentioning
confidence: 99%